Leveraging the historical experience of the GTO fitness standards to promote contemporary physical education movement in an agricultural university - Orishev, A.B.; Mamedov, A.A.; Sherstyuk, M.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to reconstruct the historical stages of the GTO fitness standards development at the Timiryazev Academy and, drawing on an analysis of contemporary students’ motivation, to identify ways of utilizing historical experience for promoting the physical education movement in an agricultural university. Methods and structure of the study. The methodological basis comprised a comparative-historical method, analysis of the university’s programme documents, and analysis of sociological survey data. The study reconstructed three key stages in the development of the programme at the Timiryazev Academy: the military-mobilisation stage; the stage of labour mobilisation and mass physical education movement; and the contemporary recreation-incentive stage, characterised by voluntariness, health preservation, and a system of material incentives. The empirical component draws on an analysis of large-scale GTO fitness testing competitions held at the academy in September 2025, involving over 800 students and 120 faculty members, enabling a comparison between historical traditions and modern practices. Results and conclusions. A sociological survey revealed a dominance of pragmatic participation motives: earning additional points and benefits (52.88% of respondents), aspiration to obtain the GTO badge as a status symbol (50.52%), and improving physical appearance (42.93%), whereas the influence of the older generation’s example (12.3%) and that of instructors (18.32%) proved the least significant. A small but important group of students – bearers of ‘historical memory’ – was identified, who may serve as ambassadors of tradition within the student community. Practical recommendations provide a rationale for a model of GTO promotion in an agricultural university based not on a direct appeal to the past, but on an organic integration of the historical foundation into a contemporary system of pragmatic incentives and rewards, including the strengthening of bonus mechanisms. The findings may be applied in developing strategies for the advancement of physical education and sport in agricultural and specialised universities, as well as in the practical work of GTO testing centres.